THE EFFECT OF MUSYARAKAH, MUDHARABAH, AND MURABAHAH FINANCING ON RETURN ON ASSET (ROA) DURING THE COVID-19 PANDEMIC (CASE STUDY ON BCA SYARIAH BANK & BUKOPIN SYARIAH KB FOR THE 2019-2021 PERIOD) - Niken Sania Putri; Meriyati Meriyati; Fadilla Fadilla; Havis Aravik; Saprida Saprida (Pusat Riset dan Inovasi Nasional, 2022)
This study discusses the Effect of Musyarakah, Mudharabah, and Murabahah Financing on Return On Assets (ROA) During the Covid-19 Pandemic. The purpose of this study was to analyze the effect of Musyarakah, Mudharabah, and Murabahah Financing on Return On Assets (ROA) during the COVID-19 pandemic at Islamic Commercial Banks (period 2019 – 2021). This research uses quantitative research methods, namely analytical methods based on calculations made by researchers. This research data is secondary data obtained from Monthly Financial Report data at Islamic Commercial Banks for the 2019-2021 period. The method used in this study is the classical assumption test, multiple linear regression analysis, and hypothesis testing assisted by the SPSS (Statistical Package For Social Science) version 26 computer program. The results of this study indicate that (1) Musyarakah financing variables partially have no positive effect. to returns on assets (ROA). (2) Mudharabah financing variable partially has a positive effect on return on assets (ROA). (3) Murabahah financing variable partially does not have a positive effect on returns on assets (ROA). (4) Musyarakah, Mudharabah, and Murabahah Financing variables simultaneously or jointly have an effect on Return On Assets (ROA) during the covid-19 pandemic.